(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2011)
In this paper I take into account the idea of reflective pictorial difference. The question is: is a pre-reflective difference a fundamental difference, to which we can answer by means of a reflective difference? I try to explain this problem with reference to Bernard Waldenfels’ responsive philosophy.